UNSUR BUDAYA MASYARAKAT JEPANG DALAM SANMAI NO OFUDA - Yuliani Rahmah (Universitas Diponegoro, 2013)
ABSTRACT This paper discusses a Japanese folktale (mukashi banashi) entitled Sanmai no Ofuda. This folktale has similarities with local folktales from several regions in Indonesia. In this paper, the writer tried to explore the condition of the society as well as the cultural backgrounds which became the setting of Sanmai no Ofuda. The writer tried to understand the cultural condition in Sanmai no Ofuda by examining the elements of the culture and the intrinsic elements. The findings show that the cultural background of the Japanese society as depicted in Sanmai no Ofuda has many similarities with the cultural background of Indonesian people. The intrinsic elements found in this study are language, system of social organization, belief, and the livelihood system. Keywords:Folktale, Cultural Background, Japan Society